On Thompson’s Conjecture for Alternating Groups Ap+3 - Shitian Liu; Yong Yang (The Scientific World Journal)
Let G be a group. Denote by π(G) the set of prime divisors of |G|. Let GK(G) be the graph with vertex set π(G) such that two primes p and q in π(G) are joined by an edge if G has an element of order p·q. We set s(G) to denote the number of connected components of the prime graph GK(G). Denote by N(G) the set of nonidentity orders of conjugacy classes of elements in G. Alavi and Daneshkhah proved that the groups, An where n=p,p+1,p+2 with s(G)≥2, are characterized by N(G). As a development of these topics, we will prove that if G is a finite group with trivial center and N(G)=N(Ap+3) with p+2 composite, then G is isomorphic to Ap+3.